ANALISIS GAYA KEPEMIMPINAN TERHADAP PENERAPAN FORMAL CONTROLUNTUK MENGATASI MOTIVATIONAL PROBLEM DI PT “W” SURABAYA - Felita Sumartono; Wiyono Pontjoharyo (Perpustakaan Universitas Surabaya, 2018)
This research aims to analyze the lingkages leadership style and formal control to resolve employee motivational problem in family business using the form explanatory research. Motivated by the dissatisfaction of factory employees to the policy of the family business entity causing the decrease of work motivation of employees, leader as a change agent is expected to be someone who can bring change by influencing others to do something including to control employee motivation. Based on these thoughts, this research considered as an interesting research. This type of research is applied research with qualitative approach method. This research trying to give recommendations with formal controls that have not been effectively and fullyapplied by looking at the leadership style so the employee motivational problem can be solved. The results showed that leaders in the business entity has the type of transformational leadership. Thisstudy also show that employees who work at the factory having problem of motivation caused by job dissatisfaction related to hygiene factors from Herzberg theory as working condition, technical supervision, pay, company policy and administration, and status. Therefore, the required action control and result control in order to adjustindividual goals and objectives of the business entity.